PELATIHAN METODE APPLIED BEHAVIORAL ANALYSIS (ABA) DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS BAGI GURU SD GUGUS III SEKACAMATAN CIAWI BOGOR - Nurmawati, Nurmawati; Ithriyah, Siti; Fadliansyah, Fadliansyah (MAJU : Indonesian Journal of Community Empowerment, 2025)
Disorders experienced by children are certainly very unpleasant, especially for parents, teachers and families because there are special limitations that are different from normal children, so parents and teachers need to provide special therapy to abnormal children which of course leads to better. Each therapy has advantages and disadvantages, for example: biomedical therapy focuses more on minimizing hyper behavior so that children can be calm. Occupational therapy helps children train the muscles of the body and legs to be strong and balanced right and left. Teacch that emphasizes children to be able to work purposefully in their community. Sensory integration therapy teaches children how to train the balance of the right and left brain so that they develop in a balanced way. Sone-rise has a main principle, namely following "whatever" the child wants to do, there is nothing wrong with the child's behavior and accepting it as it is with enthusiasm and love. The therapies above focus more on physical and minimizing hyper behavior in children, while none have focused on communication skills in children. Therefore, a comprehensive therapy is needed to help children develop. A comprehensive therapy to help children develop is Applied Behavior Analysis (ABA) therapy.In line with the various demands addressed to each teacher, with various academic requirements for a teacher, their existence is highly expected to provide learning based on the competencies that must be possessed, along with the demands of the development of the child's soul. Fulfillment of the requirements for mastering competencies as a learning agent which includes Pedagogical Competence, personality competency, social competency and professional competency can be proven through the process of achieving educational quality based on the minimum completion criteria (KKM). Thus, it is necessary to conduct training for teachers of SDN Gugus III Ciawi Bogor in improving teaching competency through the ABA method in handling children with special needs